Inovasi Media Pembelajaran Bahasa Arab melalui Flash Card untuk Meningkatkan Pemahaman Ta’bir yaumi : Inovasi Media Pembelajaran Bahasa Arab Melalui Kartu Flash untuk Meningkatkan Pemahaman Terhadap Ta'bir Yaumi - Akmal Pontoh; Sahrul Muhamad; Muh. Rizki Gobel (ELOQUENCE : Journal of Foreign Language, 2025)
Background: The development of digital technology in learning media has changed the way students interact with subject matter. However, although there have been many studies on the use of media in language learning, there is still a lack of research that specifically evaluates the effectiveness of using Flash Cards in teaching ta’bir yaumi in Arabic. Objectives: This study aims to develop Flash Card-based learning media that is effective in improving students' understanding of ta’bir yaumi. The media was designed not only to be visually appealing, but also to fulfill pedagogical principles relevant to language learning. Method: This study uses the Research and Development (R&D) method, which aims to produce a certain product while testing its effectiveness. This research has a main focus on the product development process through a series of trials and revisions to produce a product that is ready to be used effectively. In this study, the development model applied is the ADDIE model, which is considered more rational and has simple development stages. This model follows the needs of research and development conducted by researchers. Results and Discussion: At the analysis stage is a stage in analyzing the problems and needs of students. Analyze the problem to find out related problems in the learning process. At the design stage, researchers create storyboards as the first step in media design. Furthermore, at the development stage, researchers began to produce Flash Card learning media. After the media is made, validation is carried out by involving experts. The validation results showed that media experts gave a percentage of 94% (category “very feasible”), material experts 92% (category “very feasible”), and linguists 81% (category “very feasible”). At the implementation stage, the results of the teacher's assessment of this media resulted in a score of 98%, which is included in the “very feasible” category based on the eligibility criteria table. Student responses also showed a score of 98%, which is also included in the “very feasible” category. At the evaluation stage, the t-test produced a t-value of -36.582 with a degree of freedom (df) of 14 and a significance value (Sig. 2-tailed) of 0.000. This very small p-value (p < 0.05) indicates a statistically significant difference between the pre-test and post-test scores. This confirms that the use of Flash Card learning media effectively improves students' understanding of the material provided. Conclusion and Implication: This study shows that Flash Card-based learning media can significantly improve students' understanding of ta’bir yaumi in Arabic language learning. It was also shown to increase learning motivation, and student engagement, as well as the ability to recall vocabulary and colloquial expressions. The findings underscore the importance of developing creative and technology-based learning media to support the language learning process more effectively.